Structure and Function of the C-terminal Domain of the HsdR Subunit from the Type I Restriction-Modification System EcoR124 - Grinkevich, Pavel (Jihočeská univerzita, 2018)
The Type I restriction-modification enzyme EcoR124 is a pentameric complex consisting of one specificity subunit, two methylation subunits and two motor subunits (HsdR) that can recognize specific DNA sequences and perform double-stranded DNA cleavage and modification. The HsdR subunit is responsible for ATP-dependent DNA translocation and DNA cleavage. Even though the first crystal structure of HsdR was obtained ten years ago, a large part of the C-terminus has not been resolved in any HsdR structures to date. This dissertation aims to elucidate its role within the HsdR subunit and the whole pentameric complex by solving the structure of the C-terminus by means of X-ray diffraction crystallography and explore its function using biochemical, microbiological, bioinformatical and computational methods.
Structure and Function of the C-terminal Domain of the HsdR Subunit from the Type I Restriction-Modification System EcoR124
Keywords: EcoR124; restriction enzyme; restriction-modification; HsdR; motor subunit; C-terminal domain; crystal structure; X-ray crystallography; fusion protein; Escherichia coli; EcoR124; restriction enzyme; restriction-modification; HsdR; motor subunit; C-terminal domain; crystal structure; X-ray crystallography; fusion protein; Escherichia coli